A high-fog and high-light-transmittance quantum dot diffusion plate and preparation method thereof

By combining surface carboxylated quantum dot polymer composite microspheres with PEI resin, the problem of poor mixing in the prior art results in low light transmittance and haze is solved, and quantum with high light transmittance, high haze and fluorescence characteristics are achieved Point diffusion plate.

CN118562293BActive Publication Date: 2025-02-18REGENCY OPTICS ELECTRON CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410636053.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-02-18
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The existing quantum dot composite microspheres are difficult to mix well with PEI resin, and are prone to agglomeration, which affects the light transmittance and haze of the diffusing plate.

Method used

The surface carboxylated quantum dot polymer composite microspheres are used, and the mixture is melted and extruded by heating by a single screw extruder. The EDC reacts with the carboxyl groups on the surface of the microspheres to form an amide compound, which plays a defect passivation effect.

Benefits of technology

The good combination of PEI resin and quantum dot polymer composite microspheres is achieved, which improves the light transmittance and haze of the diffuser plate, and at the same time imparts the fluorescence characteristics of the diffuser plate, which is suitable for specific lighting or display applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005174584940000111
    Figure GDA0005174584940000111
Patent Text Reader

Abstract

The invention discloses a high-fog and high-light-transmittance quantum dot diffusion plate and a preparation method thereof. The high-fog and high-light-transmittance quantum dot diffusion plate comprises the following components in parts by mass: PEI resin, surface carboxylated quantum dot polymer composite microspheres, antioxidants, lubricants, light stabilizers, ultraviolet absorbers and EDC. The diffusion plate prepared by the application can simultaneously obtain high light transmittance and haze, and also by adding the component EDC, the EDC reacts with the carboxyl group on the surface of the microsphere to generate an amide compound to play a defect passivation role, thereby improving the recombination efficiency of the surface state excitons of the microspheres, so that the diffusion plate has fluorescent characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diffuser plate manufacturing, and in particular to a high-fog and high-light-transmittance quantum dot diffuser plate and a preparation method thereof. Background Art

[0002] Light diffuser, also known as light homogenizing plate, has been maturely applied in the field of liquid crystal display and LED lighting. Its main function is to fully scatter the incident light, making the light softer and more uniform. Transmittance and haze are the two main performance indicators of light diffuser. The higher the transmittance, the higher the utilization rate of light by the light diffuser; the higher the haze, the stronger the light diffusion ability of the light diffuser; light diffuser is the main factor affecting the transmittance and haze of light diffuser. When producing light diffuser, light diffuser needs to be added to the raw materials. The diffuser is evenly distributed in the plate, so that when the light passes through the plate, it encounters the light diffuser to reflect, refract, and scatter, so that the light can pass through the plate evenly, achieving the change from point light source to surface light source.

[0003] The principle of the light source changing from a point light source to a surface light source after passing through the light diffuser is that when the point light source passes through the light diffuser containing the light diffuser, if the light refractive index of the light diffuser is excessively higher or lower than the light refractive index of the substrate, it will cause a lot of reflections and affect the light transmittance. When it is close to the refractive index of the substrate, the path of light scattering will be reduced, the transparency will decrease, and it will not be able to effectively avoid light. Therefore, light transmittance and scattering must be balanced based on actual needs. Therefore, the scattering of light must be controlled within a reasonable range. Therefore, there are certain requirements and limitations for the refractive index, sphericity, particle surface regularity, particle size and concentration of the light diffuser. Therefore, as a light diffuser, the refractive index must not only be smaller than that of the substrate, but also cannot be too different from that of the substrate. Because the greater the refractive index difference, the stronger the scattering effect, and the excessive difference in the refractive index between the substrate and the light diffuser particles will cause full reflection, reflecting the light back to the inside and unable to be effectively exported.

[0004] PEI resin is an amber-colored high-performance thermoplastic polymer, which can be prepared by heating 4,4'-diaminodiphenyl ether or m-(or p-)phenylenediamine and 2,2'-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride in dimethylacetamide solvent through polycondensation and powder imidization. It has the advantages of light weight, high specific strength, heat resistance, flame retardancy, etc. It can be used as the substrate of light diffusion plate to not only meet the light diffusion requirements but also has unique advantages due to the above-mentioned various characteristics.

[0005] Quantum dots are widely used in the display field due to their wide color gamut, good thermal stability, low light loss, and particle size and refractive index that can be controlled by reaction. After quantum dots are made into composite microspheres, the refractive index is different due to the different components of the inner and outer layers of the microspheres. Therefore, they can be used as light diffusers to better transform point light sources into surface light sources, thereby achieving better light uniformity. However, the existing quantum dot composite microspheres cannot be well mixed with PEI resins, and are prone to agglomeration, which in turn affects the transmittance and haze of the diffuser. Therefore, how to combine PEI resin and quantum dot polymer composite microspheres to obtain a high-fog and high-transmittance quantum dot diffuser is a topic worth studying, and no reports on this have been seen so far. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a high-fog and high-transmittance quantum dot diffuser, which includes the following components in parts by mass: 83 to 93 parts of PEI resin, 4 to 7 parts of surface carboxylated quantum dot polymer composite microspheres, 0.2 to 0.6 parts of antioxidant, 1 to 5 parts of lubricant, 0.6 to 1.2 parts of light stabilizer, 0.4 to 0.8 parts of ultraviolet absorber, and 0.8 to 2.4 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC).

[0007] Furthermore, the preparation method of the high-fog and high-light-transmittance quantum dot diffuser plate comprises the following steps:

[0008] Preparation of surface carboxyl-grouped quantum dot polymer composite microspheres;

[0009] The surface carboxylation quantum dot polymer composite microspheres, EDC, PEI resin, antioxidant, lubricant, light stabilizer, and ultraviolet absorber are uniformly stirred to obtain a mixture A, and the mixture A is then put into a single screw extruder; then the single screw extruder is heated to melt the mixture A, and then the mixture is extruded by the single screw extruder to obtain a finished product;

[0010] Among them, the temperatures of each zone of the single-screw extruder are: zone one temperature is 300-310°C, zone two temperature is 310-320°C, zone three temperature is 310-320°C, zone four temperature is 310-320°C, zone five temperature is 325-335°C, zone six temperature is 315-325°C, zone seven temperature is 310-320°C, and the die head temperature is 305-315°C.

[0011] Further, the preparation of surface carboxylated quantum dot polymer composite microspheres comprises the following steps:

[0012] 10 to 20 parts of tert-butyl methacrylate, 8 to 10 parts of trimethylolpropane triacrylate, 0.28 to 0.68 parts of benzoyl peroxide (BPO), 10 to 14 parts of toluene and 1 to 5 parts of polyoxypropylene polyoxyethylene copolymer are mixed, 30 to 50 parts of deionized water are added under stirring, and then 3.5 to 5.5 parts of N, N-dimethylaniline (MBAM) are added to obtain a concentrated emulsion; then 1 to 2 parts of polyvinyl alcohol (PVA) and 1 to 2 parts of ammonium persulfate (APS) are added to 50 to 70 parts of deionized water, the temperature is raised to 35 to 55° C., and the concentrated emulsion is added while stirring to perform suspension polymerization, and after the particles become hard, the filter residue is filtered out, and the residue is washed with deionized water and anhydrous ethanol for several times until neutral, and dried to obtain polymer porous microspheres;

[0013] 1-3 parts of 3-mercaptopropyltrimethoxysilane are added to 12-16 parts of 40-60% ethanol aqueous solution and stirred evenly to obtain a reserve solution; 3-7 parts of hexadecyltrimethylammonium bromide, 1-3 parts of polyvinylpyrrolidone and 15-25 parts of polymer porous microspheres are added to 40-60 parts of anhydrous ethanol and stirred to disperse to obtain a polymer porous microsphere suspension; nitrogen is introduced, and 1-2 parts of anhydrous zinc acetate are added to the polymer porous microsphere suspension and stirred at the same time, and then 1-2 parts of sodium thiosulfate are added and stirred at the same time, and the pH is adjusted to 3.5-4.5 with acetic acid, and then the reserve solution is added, and the reaction is stirred at 60-80° C. for 4-8 hours; the filter is filtered again and the filter residue is collected, and the filter residue is washed with deionized water and anhydrous ethanol for several times until neutral, and dried to obtain quantum dot polymer composite microspheres;

[0014] 5-10 parts of quantum dot polymer composite microspheres are immersed in a mixed solution containing 15-25 parts of trifluoroacetic acid and 65-80 parts of dichloromethane for hydrolysis at room temperature for 20-40 minutes, then washed with dichloromethane and dried to obtain surface carboxylated quantum dot polymer composite microspheres.

[0015] Furthermore, the antioxidant is any one of antioxidant 1024, antioxidant 1010 or antioxidant 1076.

[0016] Furthermore, the lubricant is silicone oil.

[0017] Further, the light stabilizer is selected from light stabilizer 770 or light stabilizer 622.

[0018] Furthermore, the ultraviolet absorber is selected from ultraviolet absorber UV-329 or ultraviolet absorber UV-531.

[0019] The beneficial effect is that: the present invention uses tert-butyl methacrylate as a polymerization monomer and trimethylolpropane triacrylate as a crosslinking agent to prepare polymer porous microspheres, and then uses 3-mercaptopropyltrimethoxysilane and hexadecyltrimethylammonium bromide as ligands to coat the surface of the microspheres with zinc sulfide quantum dots. In this process, 3-mercaptopropyltrimethoxysilane will undergo hydrolysis and polycondensation to further coat the quantum dots and block water and oxygen, and finally obtain quantum dot polymer composite microspheres with a refractive index of 1.5286; then, the easy hydrolysis property of tert-butyl ester is utilized to coat the microspheres with zinc sulfide quantum dots. Carboxyl functional groups are introduced into the surface of the ball to obtain surface carboxyl-treated quantum dot polymer composite microspheres with a refractive index of 1.5319. Such surface carboxyl-treated quantum dot polymer composite microspheres have both the high toughness and easy processing of polymers and the rigidity, thermal stability and photoluminescence of inorganic quantum dot materials, so that light can be scattered and invisible ultraviolet light can be converted into visible light, which is conducive to the full utilization of light. The refractive index is slightly different from that of PEI resin 1.5525, so the prepared diffuser plate can simultaneously obtain high light transmittance and haze. At the same time, the present application also adds the component EDC, and utilizes the EDC to react with the carboxyl group on the surface of the microsphere to generate an amide compound to play a defect passivation role, thereby improving the recombination efficiency of the surface state excitons of the microspheres, so that the diffuser plate has fluorescent characteristics, so that the diffuser plate can diffuse light and emit fluorescence itself, and can provide a more uniform, soft light source with a specific color temperature or color effect in specific lighting or display applications. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.

[0021] The following embodiments are only used to illustrate the present invention, but are not limited to the scope of the present invention. Based on the specific embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention.

[0022] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the examples of the present invention, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.

[0023] Source of raw materials:

[0024] PEI resin, Ultem 1000, was purchased from Saudi Basic Industries Corporation;

[0025] Oil-soluble CdSe / ZnS quantum dots were purchased from Xingzi (Shanghai) New Materials;

[0026] Antioxidants were purchased from Shandong Xuxiang Chemical Co., Ltd.

[0027] Silicone oil was purchased from Jinan Xuchuang Chemical Technology Co., Ltd.

[0028] Light stabilizer, purchased from Shanghai Tiandui New Materials Co., Ltd.;

[0029] Ultraviolet absorber, purchased from Jinan Xiangfeng Weiye Chemical Co., Ltd.;

[0030] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) was purchased from Sigma-Aldrich Chemical Reagent Company;

[0031] Tert-butyl methacrylate, trimethylolpropane triacrylate, polyvinyl alcohol (PVA), hexadecyltrimethylammonium bromide, anhydrous zinc acetate Zn(CH3 COO)2, and sodium thiosulfate Na2S2O3 were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0032] Anhydrous ethanol was purchased from Xiamen Minghuiyang Chemical Co., Ltd.

[0033] Benzoyl peroxide (BPO) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0034] Toluene was purchased from Beijing Chemical Plant;

[0035] Polyoxypropylene polyoxyethylene copolymer, purchased from Zhengzhou Aikemu Chemical Co., Ltd.;

[0036] N,N-Dimethylaniline (MBAM) was purchased from Shanghai Adamas Reagent Co., Ltd.;

[0037] Ammonium persulfate (APS) was purchased from Changzhou Qidi Chemical Co., Ltd.;

[0038] 3-Mercaptopropyltrimethoxysilane was purchased from Shanghai Dingfen Chemical Technology Co., Ltd.;

[0039] Polyvinyl pyrrolidone was purchased from Shandong Xinxiong Biotechnology Co., Ltd.;

[0040] Acetic acid and trifluoroacetic acid were purchased from Jinan Jumeihui Chemical Co., Ltd.;

[0041] Dichloromethane was purchased from Shandong Gucheng Chemical Technology Co., Ltd.;

[0042] The remaining reagents are commercially available.

[0043] Example 1

[0044] The present embodiment provides a high-fog and high-transmittance quantum dot diffuser plate, which includes the following components in parts by mass: 88 parts of PEI resin, 5.5 parts of surface carboxylated quantum dot polymer composite microspheres, 0.4 parts of antioxidant, 3 parts of lubricant, 0.9 parts of light stabilizer, 0.6 parts of ultraviolet absorber, and 1.6 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), wherein the antioxidant is antioxidant 1024, the lubricant is silicone oil, the light stabilizer is light stabilizer 770, and the ultraviolet absorber is ultraviolet absorber UV-329.

[0045] The preparation method of the high-fog and high-light-transmittance quantum dot diffuser plate comprises the following steps:

[0046] Preparation of surface carboxyl-grouped quantum dot polymer composite microspheres;

[0047] The surface carboxylation quantum dot polymer composite microspheres, EDC, PEI resin, antioxidant, lubricant, light stabilizer, and ultraviolet absorber are uniformly stirred to obtain a mixture A, and the mixture A is then put into a single screw extruder; then the single screw extruder is heated to melt the mixture A, and then the mixture is extruded by the single screw extruder to obtain a finished product;

[0048] Among them, the temperature of each zone of the single screw extruder is: the temperature of zone 1 is 305℃, the temperature of zone 2 is 315℃, the temperature of zone 3 is 315℃, the temperature of zone 4 is 315℃, the temperature of zone 5 is 330℃, the temperature of zone 6 is 320℃, the temperature of zone 7 is 315℃, and the temperature of the die head is 310℃;

[0049] The preparation of surface carboxylated quantum dot polymer composite microspheres comprises the following steps:

[0050] 15 parts of tert-butyl methacrylate, 9 parts of trimethylolpropane triacrylate, 0.48 parts of benzoyl peroxide (BPO), 12 parts of toluene and 3 parts of polyoxypropylene polyoxyethylene copolymer are mixed, 40 parts of deionized water are added under stirring, and then 4.5 parts of N,N-dimethylaniline (MBAM) are added to obtain a concentrated emulsion; then 1.5 parts of polyvinyl alcohol (PVA) and 1.5 parts of ammonium persulfate (APS) are added to 60 parts of deionized water, the temperature is raised to 45°C, and the concentrated emulsion is added while stirring to carry out suspension polymerization, and after the particles become hard, the residue is filtered and washed with deionized water and anhydrous ethanol for several times until neutral, and dried to obtain polymer porous microspheres;

[0051] 2 parts of 3-mercaptopropyltrimethoxysilane are added to 14 parts of 50% ethanol aqueous solution and stirred evenly to obtain a reserve solution; 5 parts of hexadecyltrimethylammonium bromide, 2 parts of polyvinylpyrrolidone and 20 parts of polymer porous microspheres are added to 50 parts of anhydrous ethanol and stirred to disperse to obtain a polymer porous microsphere suspension; nitrogen gas with a flow rate of 50 mL / min is introduced, and 1.5 parts of anhydrous zinc acetate are added to the polymer porous microsphere suspension and stirred at the same time, and then 1.5 parts of sodium thiosulfate are added and stirred at the same time, and the pH is adjusted to 4 with acetic acid, and then the reserve solution is added, and the reaction is stirred at 70°C for 6 hours; the filter is filtered again and the filter residue is collected, and the filter residue is washed with deionized water and anhydrous ethanol for several times until neutral, and dried to obtain quantum dot polymer composite microspheres;

[0052] 7.5 parts of quantum dot polymer composite microspheres were immersed in a mixture of 20 parts of trifluoroacetic acid and 72.5 parts of dichloromethane for hydrolysis at room temperature for 30 minutes, then washed with dichloromethane and dried to obtain surface carboxylated quantum dot polymer composite microspheres.

[0053] Example 2

[0054] The present embodiment provides a high-fog and high-transmittance quantum dot diffuser plate, which includes the following components in parts by mass: 83 parts of PEI resin, 7 parts of surface carboxylated quantum dot polymer composite microspheres, 0.6 parts of antioxidant, 5 parts of lubricant, 1.2 parts of light stabilizer, 0.8 parts of ultraviolet absorber, and 2.4 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), wherein the antioxidant is antioxidant 1010, the lubricant is silicone oil, the light stabilizer is light stabilizer 622, and the ultraviolet absorber is ultraviolet absorber UV-531.

[0055] The preparation method of the high-fog and high-light-transmittance quantum dot diffuser plate comprises the following steps:

[0056] Preparation of surface carboxyl-grouped quantum dot polymer composite microspheres;

[0057] The surface carboxylation quantum dot polymer composite microspheres, EDC, PEI resin, antioxidant, lubricant, light stabilizer, and ultraviolet absorber are uniformly stirred to obtain a mixture A, and the mixture A is then put into a single screw extruder; then the single screw extruder is heated to melt the mixture A, and then the mixture is extruded by the single screw extruder to obtain a finished product;

[0058] Among them, the temperature of each zone of the single screw extruder is: the temperature of zone 1 is 300℃, the temperature of zone 2 is 310℃, the temperature of zone 3 is 310℃, the temperature of zone 4 is 310℃, the temperature of zone 5 is 325℃, the temperature of zone 6 is 315℃, the temperature of zone 7 is 310℃, and the temperature of the die head is 305℃;

[0059] The preparation of surface carboxylated quantum dot polymer composite microspheres comprises the following steps:

[0060] 10 parts of tert-butyl methacrylate, 10 parts of trimethylolpropane triacrylate, 0.68 parts of benzoyl peroxide (BPO), 14 parts of toluene and 5 parts of polyoxypropylene polyoxyethylene copolymer are mixed, 50 parts of deionized water are added under stirring, and then 5.5 parts of N,N-dimethylaniline (MBAM) are added to obtain a concentrated emulsion; then 2 parts of polyvinyl alcohol (PVA) and 2 parts of ammonium persulfate (APS) are added to 70 parts of deionized water, the temperature is raised to 55° C., and the concentrated emulsion is added while stirring to carry out suspension polymerization, and after the particles become hard, the residue is filtered and washed with deionized water and anhydrous ethanol for several times until neutral, and dried to obtain polymer porous microspheres;

[0061] 3 parts of 3-mercaptopropyltrimethoxysilane are added to 16 parts of 60% ethanol aqueous solution and stirred evenly to obtain a reserve solution; 7 parts of hexadecyltrimethylammonium bromide, 3 parts of polyvinylpyrrolidone and 25 parts of polymer porous microspheres are added to 60 parts of anhydrous ethanol and stirred to disperse to obtain a polymer porous microsphere suspension; nitrogen gas with a flow rate of 50 mL / min is introduced, and 2 parts of anhydrous zinc acetate are added to the polymer porous microsphere suspension and stirred at the same time, and then 2 parts of sodium thiosulfate are added and stirred at the same time, and the pH is adjusted to 4.5 with acetic acid, and then the reserve solution is added, and the reaction is stirred at 80°C for 8 hours; the filter is filtered again and the filter residue is collected, and the filter residue is washed with deionized water and anhydrous ethanol for several times until neutral, and dried to obtain quantum dot polymer composite microspheres;

[0062] 10 parts of quantum dot polymer composite microspheres were immersed in a mixture of 25 parts of trifluoroacetic acid and 80 parts of dichloromethane for hydrolysis at room temperature for 40 minutes, then washed with dichloromethane and dried to obtain surface carboxylated quantum dot polymer composite microspheres.

[0063] Example 3

[0064] The present embodiment provides a high-fog and high-transmittance quantum dot diffuser plate, which includes the following components in parts by mass: 93 parts of PEI resin, 4 parts of surface carboxylated quantum dot polymer composite microspheres, 0.2 parts of antioxidant, 1 part of lubricant, 0.6 parts of light stabilizer, 0.4 parts of ultraviolet absorber, and 0.8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), wherein the antioxidant is antioxidant 1076, the lubricant is silicone oil, the light stabilizer is light stabilizer 770, and the ultraviolet absorber is ultraviolet absorber UV-329.

[0065] The preparation method of the high-fog and high-light-transmittance quantum dot diffuser plate comprises the following steps:

[0066] Preparation of surface carboxyl-grouped quantum dot polymer composite microspheres;

[0067] The surface carboxylation quantum dot polymer composite microspheres, EDC, PEI resin, antioxidant, lubricant, light stabilizer, and ultraviolet absorber are uniformly stirred to obtain a mixture A, and the mixture A is then put into a single screw extruder; then the single screw extruder is heated to melt the mixture A, and then the mixture is extruded by the single screw extruder to obtain a finished product;

[0068] Among them, the temperature of each zone of the single screw extruder is: the temperature of zone 1 is 315℃, the temperature of zone 2 is 320℃, the temperature of zone 3 is 320℃, the temperature of zone 4 is 320℃, the temperature of zone 5 is 335℃, the temperature of zone 6 is 325℃, the temperature of zone 7 is 320℃, and the temperature of the die head is 315℃;

[0069] The preparation of surface carboxylated quantum dot polymer composite microspheres comprises the following steps:

[0070] 20 parts of tert-butyl methacrylate, 8 parts of trimethylolpropane triacrylate, 0.28 parts of benzoyl peroxide (BPO), 10 parts of toluene and 1 part of polyoxypropylene polyoxyethylene copolymer are mixed, 30 parts of deionized water are added under stirring, and then 3.5 parts of N,N-dimethylaniline (MBAM) are added to obtain a concentrated emulsion; then 1 part of polyvinyl alcohol (PVA) and 1 part of ammonium persulfate (APS) are added to 50 parts of deionized water, the temperature is raised to 35°C, and the concentrated emulsion is added while stirring to perform suspension polymerization, and after the particles become hard, the residue is filtered and washed with deionized water and anhydrous ethanol for several times until neutral, and dried to obtain polymer porous microspheres;

[0071] Add 1 part of 3-mercaptopropyltrimethoxysilane to 12 parts of 40% ethanol aqueous solution and stir evenly to obtain a reserve solution; take 3 parts of hexadecyltrimethylammonium bromide, 1 part of polyvinylpyrrolidone and 15 parts of polymer porous microspheres and add them to 40 parts of anhydrous ethanol and stir and disperse to obtain a polymer porous microsphere suspension; introduce nitrogen at a flow rate of 50 mL / min, add 1 part of anhydrous zinc acetate to the polymer porous microsphere suspension and stir at the same time, then add 1 part of sodium thiosulfate and stir at the same time, adjust the pH to 3.5 with acetic acid, then add the reserve solution, and stir and react at 60°C for 4 hours; filter and collect the filter residue again, wash the filter residue with deionized water and anhydrous ethanol several times until neutral, and dry to obtain quantum dot polymer composite microspheres;

[0072] 5 parts of quantum dot polymer composite microspheres were immersed in a mixture of 15 parts of trifluoroacetic acid and 65 parts of dichloromethane for hydrolysis at room temperature for 20 minutes, then washed with dichloromethane and dried to obtain surface carboxylated quantum dot polymer composite microspheres.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 1 is that 88 parts of GPPS resin are used to replace 88 parts of PEI resin when preparing the high-fog and high-transmittance quantum dot diffuser plate, and the other components and experimental steps are the same as those in Example 1.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 1 is that when preparing the high-fog and high-transmittance quantum dot diffuser plate, 1.5 parts of oil-soluble CdSe / ZnS quantum dots are used to replace 1.5 parts of surface carboxyl-grouped quantum dot polymer composite microspheres in Example 1, and the other ingredients and experimental steps are the same as those in Example 1.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 1 is that when preparing the high-fog and high-transmittance quantum dot diffuser plate, the 0.4 parts of antioxidant is increased to 2 parts, and EDC is not added. The other ingredients and experimental steps are the same as those in Example 1.

[0079] Comparative Example 4

[0080] The difference between this comparative example and Example 1 is that when preparing the high-fog and high-light-transmittance quantum dot diffuser plate, 1.5 parts of non-surface carboxyl-grouped quantum dot polymer composite microspheres are substituted for 1.5 parts of surface carboxyl-grouped quantum dot polymer composite microspheres in Example 1.

[0081] The diffuser plates prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested.

[0082] Test method:

[0083] Both transmittance and haze are tested by a haze meter according to ASTM D1003 standard; transmittance is defined as the ratio of transmitted light to incident light; haze is the percentage of light transmittance that deviates from the incident direction due to scattering when the transmitted light passes through the sample;

[0084] The center brightness and average brightness are tested according to GY / T 326-2019 standard;

[0085] Water barrier performance is usually characterized by water vapor transmission rate (GB / T 1037), which is usually measured at 38℃ / 90RH to measure the mass of water vapor permeating through a unit area of ​​the film, in units of g / (m 2 24h);

[0086] The oxygen barrier performance is characterized by oxygen transmission rate (GB / T 1038), which measures and calculates the volume of oxygen that passes through the sample within 24 hours, in cm 3 / (m 2 ·24h·0.1MPa);

[0087] Brightness retention rate test method: Place the quantum dot diffusion plate at 60°C and 90% RH humidity for 1000 hours, detect the brightness values ​​before and after placement, and calculate the brightness retention rate, brightness retention rate = (brightness value after aging / brightness value before aging) * 100%;

[0088] Brightness and color point detection method: Place the quantum dot diffusion plate under the blue light LED module, and use the CA-310 color analyzer to test the center point brightness, color point X, and color point Y. The current is fixed at 174mA and the voltage is fixed at 8.3V.

[0089] Fluorescence detection method: Use darkroom inspection, place the diffuser in a completely dark environment, and use ultraviolet light to illuminate it. If the diffuser contains fluorescent material, it will emit visible light under the excitation of ultraviolet light, and you can intuitively judge whether there is a fluorescent effect.

[0090] The test results are shown in Table 1.

[0091] From the experimental data in Table 1, the high-fog and high-transmittance quantum dot diffuser plates prepared in each embodiment of the present application have a transmittance and haze of more than 85%, indicating that the transmittance and haze of each embodiment are good, which may be related to the microsphere structure. The surface carboxylated quantum dot polymer composite microspheres in the present application are a core-shell structure with different internal and external components. This structure can cause multiple refractions of light, and its refractive index is 1.5319, which is slightly different from the refractive index of PEI resin 1.5525. Therefore, the prepared diffuser can simultaneously obtain high transmittance and haze; Continuing to analyze the data from Table 1, it can be seen that the coordinate X offset and color coordinate Y offset of each embodiment are excellent, indicating that the luminescence of each embodiment is stable; the water vapor permeability is less than 0.5g / (m 2 ·24h), oxygen permeability coefficient is less than 0.6cm 3 / (m 2 ·24h·0.1MPa), indicating that each embodiment has high water and oxygen barrier property; the three embodiments can emit fluorescence. Further analysis shows that although the data of the three groups of embodiments are excellent, the data of embodiment 1 show that the diffuser has the best performance. It can be seen that the different proportions of the components have a certain influence on the performance of the diffuser. In actual production applications, especially in the pilot scale-up stage, it is necessary to flexibly adjust the proportions of each group according to the actual situation to obtain products with excellent comprehensive performance.

[0092] Table 1 Diffuser plate performance test results

[0093]

[0094] Combined with the comparative analysis of the various data of the comparative examples, it was found that after the comparative example 1 replaced the PEI resin with GPPS resin, the GPPS resin had poor compatibility with the surface carboxylation quantum dot polymer composite microspheres and the refractive index difference between the two was too large, resulting in poor light transmittance and haze of the diffuser plate, and low water and oxygen barrier properties. However, due to the reaction of the surface carboxylation quantum dot polymer composite microspheres with EDC, the diffuser plate prepared in comparative example 1 still had fluorescence, but the fluorescence was weaker than that of the embodiment. This may be because the GPPS resin had poor compatibility with the surface carboxylation quantum dot polymer composite microspheres, and some materials agglomerated to form an obstruction. Continuing to analyze the data in Table 1, it was found that after the comparative example 2 replaced the surface carboxylation quantum dot polymer composite microspheres in Example 1 with oil-soluble CdSe / ZnS quantum dots, the oil-soluble CdSe / ZnS quantum dots also had poor compatibility with the PEI resin and the refractive index difference between the two was too large, resulting in poor light transmittance and haze of the diffuser plate. The results show that the diffusion plate prepared in Comparative Example 2 has no fluorescence because the oil-soluble CdSe / ZnS quantum dots cannot react with EDC. The data of Comparative Example 3 show that since EDC is not added in Comparative Example 3, the diffusion plate prepared in Comparative Example 3 also has no fluorescence. However, since surface carboxylation quantum dot polymer composite microspheres and PEI resin are normally added in Comparative Example 3, the diffuser plate prepared in Comparative Example 3 has high transmittance and haze. The data of Comparative Example 4 show that the diffuser plate prepared using non-surface carboxylation quantum dot polymer composite microspheres also has good haze and transmittance. This may be because the refractive index of non-surface carboxylation quantum dot polymer composite microspheres is 1.5286, which is very close to the refractive index of PEI resin 1.5525. However, the diffuser plate prepared in Comparative Example 4 has no fluorescence, which may be because the non-surface carboxylation quantum dot polymer composite microspheres cannot react with EDC.

[0095] The above is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A high-fog and high-transmittance quantum dot diffuser plate, characterized in that: The composition includes the following components in parts by mass: 83-93 parts of polyetherimide resin, 4-7 parts of surface carboxylated quantum dot polymer composite microspheres, 0.2-0.6 parts of antioxidant, 1-5 parts of lubricant, 0.6-1.2 parts of light stabilizer, 0.4-0.8 parts of ultraviolet absorber, and 0.8-2.4 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; The preparation of the surface carboxylated quantum dot polymer composite microspheres comprises the following steps: 10-20 parts of tert-butyl methacrylate, 8-10 parts of trimethylolpropane triacrylate, 0.28-0.68 parts of benzoyl peroxide, 10-14 parts of toluene and 1-5 parts of polyoxypropylene polyoxyethylene copolymer are mixed, 30-50 parts of deionized water are added under stirring, and then 3.5-5.5 parts of N,N-dimethylaniline are added to prepare a concentrated emulsion; then 1-2 parts of polyvinyl alcohol and 1-2 parts of ammonium persulfate are added to 50-70 parts of deionized water, the temperature is raised to 35-55° C., and the concentrated emulsion is added while stirring to carry out suspension polymerization, and after the particles become hard, the filter residue is filtered out, and the residue is washed with deionized water and anhydrous ethanol for several times until neutral, and dried to obtain polymer porous microspheres; 1-3 parts of 3-mercaptopropyltrimethoxysilane are added to 12-16 parts of 40-60% ethanol aqueous solution and stirred to obtain a reserve solution; 3-7 parts of hexadecyltrimethylammonium bromide, 1-3 parts of polyvinylpyrrolidone and 15-25 parts of the polymer porous microspheres are added to 40-60 parts of anhydrous ethanol and stirred to disperse to obtain a polymer porous microsphere suspension; Passing nitrogen, adding 1-2 parts of anhydrous zinc acetate to the polymer porous microsphere suspension and stirring at the same time, then adding 1-2 parts of sodium thiosulfate and stirring at the same time, adjusting the pH to 3.5-4.5 with acetic acid, then adding the reserve solution, stirring and reacting at 60-80° C. for 4-8 hours; filtering again and collecting the filter residue, washing the filter residue with deionized water and anhydrous ethanol for several times until neutral, and drying to obtain quantum dot polymer composite microspheres; The 5-10 parts of quantum dot polymer composite microspheres are immersed in a mixed solution containing 15-25 parts of trifluoroacetic acid and 65-80 parts of dichloromethane for hydrolysis at room temperature for 20-40 minutes, then washed with dichloromethane, and dried to obtain the surface carboxylated quantum dot polymer composite microspheres.

2. The high-fog and high-transmittance quantum dot diffuser plate according to claim 1, characterized in that: The antioxidant is any one of antioxidant 1024, antioxidant 1010 or antioxidant 1076.

3. The high-fog and high-transmittance quantum dot diffuser plate according to claim 1, characterized in that: The lubricant is silicone oil.

4. The high-fog and high-transmittance quantum dot diffuser plate according to claim 1, characterized in that: The light stabilizer is selected from light stabilizer 770 or light stabilizer 622.

5. The high-fog and high-transmittance quantum dot diffuser plate according to claim 1, characterized in that: The ultraviolet absorber is selected from ultraviolet absorber UV-329 or ultraviolet absorber UV-531.

6. The method for preparing the high-fog and high-transmittance quantum dot diffuser plate according to claim 1, characterized in that: The following steps are involved: The surface carboxylation-containing quantum dot polymer composite microspheres are prepared according to the step of preparing surface carboxylation-containing quantum dot polymer composite microspheres according to claim 1; The surface carboxylation quantum dot polymer composite microspheres, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, polyetherimide resin, antioxidant, lubricant, light stabilizer, and ultraviolet absorber are uniformly stirred to obtain a mixture A, and the mixture A is then put into a single screw extruder; then the single screw extruder is heated to melt the mixture A, and then the mixture A is extruded by the single screw extruder to obtain a finished product; Among them, the temperatures of each zone of the single-screw extruder are: zone one temperature is 300~310℃, zone two temperature is 310~320℃, zone three temperature is 310~320℃, zone four temperature is 310~320℃, zone five temperature is 325~335℃, zone six temperature is 315~325℃, zone seven temperature is 310~320℃, and the die head temperature is 305~315℃.

Citation Information

Patent Citations

  • Quantum dot fluorescent microspheres and preparation method thereof

    CN109233836A

  • Quaternized polydentate ligand modified quantum dot as well as preparation method and application thereof

    CN112779000A